The Incidence Of Recurrent Laryngeal Nerve Injury During Thyroid Surgery - Hindosh, Laith; Alnasr, Mumtaz; Rassam, Raid E. (AL-Kindy College Medical Journal, 2011)
Background: Recurrent laryngeal nerve injury isan important post-thyroidectomy complication forwhich different modalities of treatment werepracticed to lower its incidence.Objectives: To estimate the incidence ofrecurrent laryngeal nerve injury in thyroid surgeriesin relation to type of surgery, type of gland diseases& nerve identification.Methods: Different types of goiters preparedpreoperatively by indirect laryngoscopy, operatedupon with different types of surgeries, postoperativedirect laryngoscopy by the anaesthetist were doneand indirect laryngoscopy done as needed.Results: Of of 200 patients, the overall incidenceof recurrent laryngeal nerve injury was 9Patients (4.5%), 7 patients (77.8%) were unilateralnerve injury & 2 patients (22.2%) were bilateralnerve injury. The percent of temporary nerve injurywas 8 patients (88.89%) & permanent injury 1patient (11.11%).the incidence of injury in femaleswas (4.57%) & in males was (4%). Injury was 1patient out of 13 (7.69%) in total thyroidectomy, 1patient out of 11 (9.09%) in completionthyroidectomy. Injury in malignant goiter was 2patients (10%).finally it was higher if nerve was notidentified (6.15%) than if identified (1.42%).Conclusion: Recurrent laryngeal nerve injury ismore in malignant goiters, in more extensivesurgery & if peroperative nerve identification wasnot practiced.